Albumin-linked prostate-specific antigen-activated thapsigargin- and niclosamide-based molecular grenades targeting the microenvironment in metastatic castration-resistant prostate cancer - Emmanuel S. Akinboye; W. Nathaniel Brennen; Samuel R. Denmeade; John T. Isaacs (Asian Journal of Urology)
Localized prostate cancer is curable via annihilation of the entire cancer neighborhood by surgery or local radiation. Unfortunately, once metastatic, no available therapy is curative. The vast majority will die despite aggressive systemic combinational androgen-ablation therapies. Thus, there is an urgent need for effective systemic therapeutics that sterilize the entire microenvironment in metastatic castration-resistant prostate cancer (mCRPC). To accomplish this goal, advantage can be taken of the unique biology of mCRPC cells. Like their normal cell of origin, mCRPCs retain expression of the prostate-specific differentiation protein, prostate-specific antigen (PSA), which they abundantly secrete into their extracellular fluid (ECF). This unique, and essentially universal, secretion of enzymatically active PSA into the ECF by mCRPCs creates an exploitable therapeutic index for activation of systemically delivered highly lipophilic toxins as “molecular grenades” covalently linked to cysteine-34 of human serum albumin (HSA) via a stable maleimide containing PSA cleavable peptide such that PSA-dependent hydrolysis (i.e., “detonation”) releases the grenades restrictively within the ECF of mCRPC. This approach decreases dose-limiting host toxicity while enhancing plasma half-life from minutes to days (i.e., pharmacokinetic effect) and increasing the tissue concentration of the maleimide coupled albumin delivery (MAD) in the ECF at sites of cancer due to the enhanced permeability of albumin at these sites (i.e., enhanced permeability and retention effect). This allows the MAD-PSA detonated grenades to circulate throughout the body in a non-toxic form. Only within sites of mCRPC is there a sufficiently high level of enzymatically active PSA to efficiently “pull the pin” on the grenades releasing their lipophilic cell-penetrant toxins from HSA. Thus, if a sufficient level of “detonation” occurs, this will kill mCRPC cells, and sterilize the entire PSA-rich metastatic sites via a bystander effect. In this review, two examples of such MAD-PSA detonated molecular grenades are presented—one based upon thapsigagin and the other on niclosamide. Keywords: Albumin-linked prodrug, Maleimide coupled albumin delivery, Thapsigargin, Niclosamide